DIBALIK KEBERLANJUTAN SAWIT: AKTOR, ALIANSI DALAM EKONOMI POLITIK SERTIFIKASI UNI EROPA - Erman, Erwiza (Masyarakat Indonesia, 2018)
Environmental sustainability and social justice are the two key principles of global oil palm certification (RSPO) that the country of export of palm oil to the European Union (EU) must adhere to. Therefore, the success or failure of palm oil trade from Indonesia and Malaysia to the EU depends on the fulfillment of these criteria. In reality, the issue of fulfilling these criteria has become an ‘entrance’ for international civil society movements to launch a black campaign in the European Union. This article tries to explain the role of actors and their alliances in palm oil producing countries, Indonesia and Malaysia in response to the implementation of the RSPO and black campaigns in Europe. Combining literary studies and in-depth interviews, this study shows that actors from palm oil producing countries have a strong role in the bargaining process to get the RSPO certificate. They are very active in giving criticism to the RSPO’s weaknesses, and even establish counter-certificates, in Indonesia called ISPO and in Malaysia with MSPO. Behind the issue of unsustainability and social injustice as principal elements of global certification, there is trade competition between palm oil producing countries and countries in European Union that produce vegetable oils such as sunflower and rapeseed oils.